Effects of compassion-focused therapy on self-criticism in university student with social anxiety: A single case study - Lee, Yi Hui (2024)

(untitled)
Engaging in self-compassion has been shown to yield numerous health benefits, including increased emotional resilience, enhanced psychological well-being, and decreased self-criticism. In line with this, the present study seeks to explore the effects of Compassion-Focused Therapy (CFT) on self-criticism in university students with social anxiety. Conducted as a single case study within a university counselling room in Malaysia, the research focused on a sole participant, a 23-year-old Chinese male Malaysian undergraduate student. The study utilized the Forms of Self-Criticising/Attacking and Self-Reassuring Scale (FSCRS) and the Liebowitz Social Anxiety Scale (LSAS) as measurement instruments. The researcher administered pre-test and post-test assessments both before and after the intervention sessions. Results indicated a significant reduction in self-criticism following CFT intervention, although no observable improvement was noted in social anxiety. In summary, the study highlights how the components and techniques of CFT can lead to changes in thought patterns and behaviors associated with self-criticism. These findings contribute valuable insights to the application of CFT among Malaysian undergraduate students, offering a reference for future research in this domain.